Use or protect - environment capital and regional development in the rural areas of Europe. Research findings and experiences from the EU project DERREG. - (:unkn) unknown (My University, 2013)
Natural resources such as clean air, water, soil, woods or special landscape features are increasingly recognized as important assets for the development of rural regions and are included in rural development strategies. The case studies presented in this volume are first results of a research project on globalization and rural development ('Developing Europe's Rural Regions in the Era of Globalization - DERREG') that has been funded under the Seventh Framework Programme of the European Union. The main research objective of the DERREG project is thus the integrative analysis of the challenges posed for rural regions by globalization. This research approach takes into consideration that globalisation is a multi-dimensional process with economic, social, cultural, political dimensions. The five case studies on the exploitation and protection of environmental resources and regional development come from four European countries: the Czech Republic, Germany, Ireland and Slovenia. The case studies cover three different general themes: the management of rural landscapes, the forestry sector and energy production.
Keywords: Regionalentwicklung; Regionalplanung; Ländlicher Raum; Region; Landschaftsschutz; Naturschutzgebiet; Umweltschutz; Forstwirtschaft; EU-Programm; Biosphärenreservat; Globalisierung; Wirkung; Nachhaltige Entwicklung